Pengaruh Persepsi Kemudahan Penggunaan terhadap Loyalitas Pelanggan Fintech (Studi Kasus Pada Pengguna Fintech di Kota Bandung) - Rudini Faina Dewi; Riauli Susilawaty Hutapea; Arry Irawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The use of financial technology is familiar to the people of Bandung City, especially in digital payments. This study aims to determine the effect of perceived ease of use on customer loyalty to financial technology users in Bandung. The data in this study were obtained through questionnaires distributed through social media platforms and the data obtained would be analyzed using simple linear regression with SPSS. The results of this study prove that the perception of convenience has a positive effect on user loyalty by 38.3%. This study is also expected to provide benefits to financial technology companies in order to improve their services.